DIGITALISASI ARSIP DALAM MENDUKUNG PELAKSANAAN E-GOVERNMENT - Lolytasari Lolytasari; Ardela Dirsanala (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2023)
E-Government is a government-issued policy to increase access to open information for digital-based communities. Higher education through the Higher Education Archives Institute seeks to implement an e-government system by joining the National Archival Information Network (JIKN) and the National Archival Information System (SIKN). On the other hand, to implement this, Higher Education Archives Institutions need to digitize their previously conventional archives. Old media has become digital, the results of which can be accessed by the public. Digitizing archives is one of the tasks of the Higher Education Archives Institution to provide information on the track record of higher education, starting from its founding to its development. This study aims to analyze the management of digitization of archives carried out by the Archives Office of the University of North Sumatra in supporting the implementation of e-Government and the utilization of an information network system that is used as an archive access portal. The research method used is descriptive with a qualitative approach which aims to obtain an overview of archive digitization management activities at the Archives Office of the University of North Sumatra. The results showed that digitizing the archives of the University of North Sumatra was carried out by transferring vital historical archives contained in photographs, cassette tapes, and VHS tapes, Betamax (old media). Then the University of North Sumatra Archives became a member of JIKN and SIKN to support the implementation of e-Government. This study recommends that archival research researchers start to create a grand design for digitizing archives with high value as a source of knowledge. Then, this research will be helpful for policymakers and all stakeholders to manage the digitization of university archives.